Clofibric Acid Increases the Formation of Oleic Acid in Endoplasmic Reticulum of the Liver of Rats - Akihiko Hirose; Tohru Yamazaki; Takeshi Sakamoto; Katsuyoshi Sunaga; Tadashi Tsuda; Atsushi Mitsumoto; Naomi Kudo; Yoichi Kawashima (Elsevier, 2011)
Abstract.: The effects of 2-(4-chlorophenoxy)-2-methylpropionic acid (clofibric acid) on the formation of oleic acid (18:1) from stearic acid (18:0) and utilization of the 18:1 formed for phosphatidylcholine (PC) formation in endoplasmic reticulum in the liver of rats were studied in vivo. [14C]18:0 was intravenously injected into control Wistar male rats and rats that had been fed on a diet containing 0.5% (w/w) clofibric acid for 7 days; and the distribution of radiolabeled fatty acids among subcellular organelles, microsomes, peroxisomes, and mitochondria, was estimated on the basis of correction utilizing the yields from homogenates of marker enzymes for these organelles. The radioactivity was mostly localized in microsomes and the radiolabeled fatty acids present in microsomes were significantly increased by the treatment of rats with clofibric acid. The formation of radiolabeled 18:1 in microsomes markedly increased and incorporations of the formed [14C]18:1 into PC and phosphatidylethanolamine in microsomes were augmented in response to clofibric acid. The [14C]18:1 incorporated into PC was mostly located at the C-2 position, but not the C-1 position, of PC, and the radioactivity in 18:1 at the C-2 position of PC was strikingly increased by clofibric acid. These results obtained from the in vivo experiments directly link the findings that clofibric acid treatment induces microsomal stearoyl-CoA desaturase and 1-acylglycerophosphocholine acyltransferase in the liver and the findings that the treatment with the drug elevated absolute mass and mass proportion of 18:1 at the C-2 position, but not the C-1 position, of PC in the liver together. Keywords:: clofibric acid, stearoyl-CoA desaturation, oleic acid, phosphatidylcholine, endoplasmic reticulum